Clinical and psychological telemonitoring and telecare of high risk heart failure patients. (December 2014) - Villani, Alessandra; Malfatto, Gabriella; Compare, Angelo; Rosa, Francesco Della; Bellardita, Lara; Branzi, Giovanna; Molinari, Enrico; Parati, Gianfranco
We conducted a trial of telemonitoring and telecare for patients with chronic heart failure leaving hospital after being treated for clinical instability. Eighty patients were randomized before hospital discharge to a usual care group (n = 40: follow-up at the outpatient clinic) or to an integrated management group (n = 40: patients learned to use a handheld PDA and kept in touch daily with the monitoring centre). At enrolment, the groups were similar for all clinical variables. At one-year follow-up, integrated management patients showed better adherence, reduced anxiety and depression, and lower NYHA class and plasma levels of BNP with respect to the usual care patients (e.g. NYHA class 2.1 vs 2.4, P  < 0.02). Mortality and hospital re-admissions for congestive heart failure were also reduced in integrated management patients ( P  < 0.05). Integrated management was more expensive than usual care, although the cost of adverse events was 42% lower. In heart failure patients at high risk of relapse, the regular acquisition of simple clinical information and the possibility for the patient to contact the clinical staff improved drug titration, produced better psychological status and quality of life, and reduced hospitalizations for heart failure.